(untitled) (Bangkok, 2013)
Content: introduction to commericial seaweeds; seadweeds used as a source of agar; agar; seaweeds used as a source of alginate...
Keywords: Forest ecology,Forests and forestry,Mangrove forests,Sinh thái rừng,Rừng và lâm nghiệp,Rừng ngập mặn